Are TiO2-based exterior paints useful catalysts for gas-phase photooxidation processes? A case study on n-decane abatement for air detoxification - Ricardo A. R. Monteiro (2014)
n-Decane is a saturated long-chain hydrocarbon, belonging to the family of the volatile organic compounds (VOCs), which is persistently present in indoor air of several industrial closed facilities. Due to the VOCs environmental impact, all efforts that have been made during the last decades to degrade this kind of air pollutants are extremely important. Accordingly, the present paper reports n-decane photooxidation studies carried out in an annular photoreactor under simulated solar irradiation and employing a catalytic bed made of cellulose acetate monoliths coated with a photocatalytic paint. The influence of the feed flow rate, n-decane concentration, relative humidity, and incident irradiance on the n-decane degradation kinetics was assessed. Within this work, n-decane photodegradations higher than 90% were achieved, depending on the experimental conditions. Additionally, a phenomenological reaction rate model of the n-decane photocatalytic oxidation was proposed and assessed. The proposed model assumes that n-decane and water molecules compete for different active sites on the catalyst surface. Finally, despite the high n-decane photodegradation achieved, reaction by-products were identified and, based on these compounds, a reaction mechanism was formulated.